Genre-Based Instruction: Improving the Students’ Skill in Writing Descriptive Text - Sukma Septian Nasution; Ahmad Jamalulael; Laksmy Ady Kusumoriny; Nur Najibah Sukmawati; Setiana Sri Wahyuni Sitepu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The objective of the study is to investigate the improvement of the students' skills in writing descriptive text by using Genre-Based Approach in seventh-grade students at MTs Daarul Muttaqien, South Tangerang. This is a Classroom Action Research with students in VII grade consisting of 22 students as subjects of the study.  The main instrument employed to collect the data is writing test supported by observation and interview to meet triangulation validity. The result showed there is an improvement in the students’ skills in writing descriptive text. It was shown from the test results where the mean score: the pre-test was 59.95 and only 22.7% of the students who passed the test. Then, it improved to 73.23 for the mean score of post test 1 that 59.1% of them passed the test. The improvement also occurred in post-test II where the mean score reaches 84.36 with a percentage of 95.5% of students who successfully did the test. The improvement was supported by the observation result that the students were active and enthusiastic in every step genre-based instruction offers. Most of the students also found it joyful and effective to improve their writing skill. In conclusion, Genre-Based Approach can improve the students’ writing skills, especially in writing descriptive text.